Relacje Aleksandra Brücknera z Romualdem Hubem: o problemie polsko-niemieckiego dialogu naukowego końca XIX wieku - Gorb, Eugen (Slavia Occidentalis, 2024)
The article focuses on the peculiarities of the research laboratory of Aleksander Brückner and Romuald Hube used in their work on the collection of texts of court oaths from the 14th and 15th centuries. The background of the history of the academic dialogue between the two scholars is based on Aleksander Brückner’s letters kept in the Jagiellonian Library. They have never been used as a source of biographical information about A. Brückner or R. Hube. On the basis of the epistolary materials and additional published sources, the author attempts to reconstruct the process of working on the publication of invaluable artefacts of the medieval Polish language.